2021
DOI: 10.3390/universe7050141
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Rays as Probes of Cosmic-Ray Propagation and Interactions in Galaxies

Abstract: Continuum gamma-ray emission produced by interactions of cosmic rays with interstellar matter and radiation fields is a probe of non-thermal particle populations in galaxies. After decades of continuous improvements in experimental techniques and an ever-increasing sky and energy coverage, gamma-ray observations reveal in unprecedented detail the properties of galactic cosmic rays. A variety of scales and environments are now accessible to us, from the local interstellar medium near the Sun and the vicinity of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 390 publications
(472 reference statements)
1
26
0
Order By: Relevance
“…CR interactions lead to the deposition of momentum and energy in their host environment (e.g. Owen et al 2018;Tibaldo et al 2021). Thus, they can become important in controlling the evolution of galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…CR interactions lead to the deposition of momentum and energy in their host environment (e.g. Owen et al 2018;Tibaldo et al 2021). Thus, they can become important in controlling the evolution of galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…One strong argument for the Galactic origin comes from the detection of gamma rays: observations of the Galaxy revealed that the Galactic disk is gamma-ray bright, which is a clear indication of the interactions of CRs with interstallar medium (ISM) material and Galactic magnetic field in the disk, and that gamma rays roughly scale with the amount of material in the disk. Moreover, observations of the Large Magellanic Cloud (LMC), located in the vicinity of our Galaxy at ∼50 kpc, have shown that the gamma-ray signal is weaker than expected given the mass of the target material in the LMC [2,3]. This reduced gamma-ray signal from the LMC can be seen as evidence that CRs are not homogeneously distributed in the Universe, and originate within our Galaxy.…”
Section: Introduction 1the Hunt For the Sources Of Galactic Cosmic Raysmentioning
confidence: 72%
“…This implies a significant change in the energy behavior of the diffuse spectrum from to at TeV energies. With the emerging Cherenkov Telescope Array (CTA) [ 63 ] and its use of more than a hundred IACTs in the Northern and Southern Hemispheres, the background will be reduced and the field of view increased to , while improving sensitivity by an order of magnitude compared to current observatories consisting of only a few ground-based Imaging Air Cherenkov Telescopes (IACTs) [ 64 ]. These enhancements from diffuse measurements of the inner Galaxy with CTA, once available, will allow verification of our model.…”
Section: Discussion In the Astrophysical Contextmentioning
confidence: 99%